Shared temperament risk factors for anorexia nervosa: a twin study. - Wade, T; Tiggemann, M; Bulik, C; Fairburn, C; Wray, N; Martin, N (2008)
OBJECTIVE: To answer two questions about the nature of the relationship between anorexia nervosa (AN) and dimensional temperament traits: Which traits are comorbid with AN? Which traits share transmitted liabilities with AN? METHODS: A community sample of 1002 same-gender female twins was selected with respect to participation in two earlier waves of data collection. Measures of eating disorder diagnoses and features were ascertained through interview and continuous measures of temperament were ascertained from self-report measures. RESULTS: Four temperaments were comorbid with AN, namely, higher levels of perfectionism (concern over mistakes, personal standards, doubt about actions), and higher need for organization. Comparison between the female co-twins of AN probands and controls (who had never had an eating disorder) showed that the former group reported higher levels of personal standards, organization, and reward dependence. The association between personal standards and reward dependence remained when controlling for the temperament of the proband or control in monozygotic twins. CONCLUSIONS: The evidence overall supports the suggestion that AN may represent the expression of a common underlying familial liability to a temperament style that reflects a striving for perfectionism, a need for order, and a sensitivity to praise and reward. The nature of the shared risk factors is likely to be, in part, genetic.